Application of Deep Breathing Relaxation and Hold Finger to Reduce Pain Levels in in Post-Laparotomy Patients with Pancreatic Head Carcinoma: Penerapan Deep Breathing Relaxation dan Hold Finger Terhadap Penurunan Tingkat Nyeri pada Pasien Karsinoma Kaput Pankreas Post-Op Laparatomi - Aprianti M, Tutty; Ramadhani, Magfirah Aulia (Essential English Grammar, 2024)
Pancreatic cancer ranks as the seventh most common cause of cancer-related death, according to the 2020 Global Cancer Statistics. This cancer can cause blockages in the duodenum or bile ducts, often requiring bypass laparotomy to relieve gastrointestinal obstructions caused by pancreatic head tumors and to restore disrupted digestive flow. Postoperative pain is common, with major surgeries typically causing more intense pain. Data shows that 70-80% of surgery patients experience postoperative pain, and 10-30% develop chronic pain. This study examines the effects of deep breathing relaxation and finger-hold therapy on changes in vital signs and pain levels. The treatment was applied for 8 minutes over 3 days, with pain monitored through vital signs. This method combines deep breathing with finger holding for 2 minutes per finger. Results showed a pain reduction from a scale of 6 to 3 on the Numeric Rating Scale, along with changes in vital signs. This intervention can be beneficial for managing postoperative pain in laparotomy patients